Childhood maltreatment and intimate partner violence perpetration in adulthood: an investigation into proximal and distal risk factors across the life course - Fedina, Lisa (Journal of family violence, 2024)
Purpose: Early experiences of childhood maltreatment have been linked to intimate partner violence (IPV) later in adulthood. Few studies, however, have examined the prospective relationship between child maltreatment and IPV perpetration in the context of proximal and distal risk factors for violence, such as depression and alcohol misuse. Method: Data from 370 adult respondents are from the Lehigh Longitudinal Study. Child maltreatment was measured prospectively at preschool ages and school-ages. Proximal and distal risk factors for adult IPV perpetration were measured in adolescence and at two time points in adulthood (age 36 and 46 years of age, on average). Hierarchical regression models were used to examine the prediction of IPV perpetration from earlier time points. Results: Results indicate that exposure to child maltreatment, frequent alcohol use in adolescence, adolescent depression, frequent alcohol use at age 36, and adult depression at age 36 are predictive of IPV perpetration at age 36. Adolescent aggression and frequent alcohol use at age 46 were significantly predictive of IPV perpetration at age 46. Conclusions: Findings identify multiple points across the life course for intervention. Interventions targeting adolescent and adult mental health and alcohol use may lessen the risk for adult IPV perpetration.